(untitled) (Historia, 2021)
Since the Gonarezhou National Park was formed in 1975, the ‘natural’ environment image of wild animals, plants and geophysical features has dominated the way it is perceived as a tourist resort and as a national heritage ‘site’. However this ‘national park’ is only a phase of the area’s history, and represents one dimension of a complex and changing perception of nature by man. In this paper I consider Gonarezhou not so much as natural space but as human-animal space in which the dominance of mankind over the last two or so centuries has imposed varying paradigms of heritage. Wildlife is a central part of these constructs, in which humankind “adapted and altered”1the environment around him/her and made it an ‘owned and controlled’ domain with or without the consent of other non-human living species. This sense of ownership, very often passed on to ‘future generations’, is what I define as heritage. It is the manner in which such ‘ownership and control’ of the wildlife environment was perceived and exercised in the pre-colonial and colonial periods that forms the crux of this paper. I argue that whereas pre-colonial space was not demarcated into separate human and game space, the first thirty years or so of colonial rule in Zimbabwe were characterized by evolving separate human-wildlife spheres that, in many ways, were influenced by contemporary wildlife policy and heritage. I view wildlife heritage not as a colonial creation but as emerging in the pre-colonial period and continuing in the colonial and post-colonial periods in a different cross-cultural and multi-racial environment.